Os chats online como fontes de materiais autênticos para a aula de PLE - Almeida, Inês Silva de; Duarte, Isabel Margarida (Linguarum Arena, 2020)
This article suggests some possibilities of using online media, more specifically messaging chats as sources for collecting examples of language use in an informal communicative context. These examples will later be used as authentic didactic materials in the Portuguese as a foreign language class. The article explores the possibilities, advantages and difficulties of collecting and using these materials, exemplifying through the work already done and experimented with Portuguese level A2/ B1 students at Johannes Gutenberg- Universität in Mainz, Germany.